2012
DOI: 10.3390/ijms13010491
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Biodegradation of Nonylphenol in the Environment

Abstract: Nonylphenol (NP) is an ultimate degradation product of nonylphenol polyethoxylates (NPE) that is primarily used in cleaning and industrial processes. Its widespread use has led to the wide existence of NP in various environmental matrices, such as water, sediment, air and soil. NP can be decreased by biodegradation through the action of microorganisms under aerobic or anaerobic conditions. Half-lives of biodegradation ranged from a few days to almost one hundred days. The degradation rate for NP was influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(69 citation statements)
references
References 93 publications
3
64
0
2
Order By: Relevance
“…It is difficult to accurately estimate uptake efficiency for both compounds in the root exposure treatments due to their instability in the hydroponic system. Previous studies have reported that BPA and NP can quickly degrade in aqueous and soil environments due to microbial action [20,30], similar to this study. Ignoring the instability issue, the total mass uptake ranged from 0.002% (tomatoes) to 0.02% (lettuce, BPA) and 0.07% (lettuce, NP) of the total amount of both contaminants applied to both crops, with roots containing the highest concentrations of each.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is difficult to accurately estimate uptake efficiency for both compounds in the root exposure treatments due to their instability in the hydroponic system. Previous studies have reported that BPA and NP can quickly degrade in aqueous and soil environments due to microbial action [20,30], similar to this study. Ignoring the instability issue, the total mass uptake ranged from 0.002% (tomatoes) to 0.02% (lettuce, BPA) and 0.07% (lettuce, NP) of the total amount of both contaminants applied to both crops, with roots containing the highest concentrations of each.…”
Section: Discussionsupporting
confidence: 89%
“…For the root exposure treatment, BPA and NP were spiked directly into the hydroponic nutrient solution. BPA and NP can be degraded efficiently by microflora in aqueous and soil environments, with half-lives of 1d or less [20,30]. This short half-life was confirmed in the hydroponic system used in the current study based on several monitoring events using an HPLC equipped with a fluorescence detector (Waters Corporation, Milford, MA).…”
Section: Exposuressupporting
confidence: 56%
“…In accordance with measured estrogenic activity, the highest concentrations of 4-iso-nonylphenols were detected at the sampling sites at Calbe and Luppe, with 16,000 mg/kg sediment and 115,000 mg/kg. A current review about the occurrence of nonylphenol in the environment was given by Mao et al [28]. A comparison of the present findings with international studies that are listed in this review shows the heavy contamination, especially of the sampling site Luppe.…”
Section: Resultsmentioning
confidence: 89%
“…Clearly, NP affects a large range of species which occupy different trophic levels of the food chain in both freshwater and marine environments. The biodegradation rate of NP is low, and it can easily accumulate in sediments of the receiving waters downstream of pollution effluents and is readily taken up by fish and aquatic invertebrates either through the gill or from benthic organisms they consume (Zou 2003, Soares et al 2008, Mao et al 2012). Because NP is both lipophilic and resistant to biodegradation, it can accumulate in a variety of fish tissues with a bioconcentration factor (BCF) from 0.9 to 35589 (Mills & Chichester 2005, Soares et al 2008.…”
Section: Discussionmentioning
confidence: 99%